(untitled) (Journal of Rangpur Medical College, 2025)
Background: Accurate knowledge of anatomy of spine with clear understanding of pedicle morphology and measurement of pedicle dimensions is crucial for treatment with pedicle screw instrumentation and that can minimize the risks of complications. Objective: The present study was carried out to find out the effect of different body weight on pedicle of lumbar vertebrae radiologically in both sexes of adult Bangladeshi people. Methods: This cross-sectional analytical study was conducted at the Department of Anatomy of Rangpur Medical College, Rangpur from a period of July 2018 to June 2019. One twenty-four (124) digital radiographs of both sex age ranging from 20 to 45 years. The vertical and horizontal diameters of the pedicles were measured in anteroposterior view of lumbar spine. Before taking radiograph, body mass index was calculated and subjects were grouped according to BMI into group A-normal weight, B-overweight, C-obese in both sexes. The data was analyzed and comparison between three groups A, B and C of both sexes was done. Result: The results showed that there were significant differences between pedicle diameters of males and females. Generally, there was a cephalocaudal increase pattern of horizontal diameters and decrease pattern of vertical diameters of both sex of different body weight. The evidence suggests that most of the pedicle’s diameters were though higher in overweight and obese but did not vary significantly. Conclusion: This data can help the surgeons for performing safe transpedicular surgeries of different body weight people of Bangladesh. J Rang Med Col. March 2025; Vol.10, No.1:16-21